Importance of being seen as a pedagogical approach among physical education teachers at a lower secondary school - an intervention case study - Ingrid Bjørklimark; Pål Lagestad (Frontiers in Education)
IntroductionThe concept of “being seen” is an educational term used in Norway related to the students feeling of being recognized and acknowledged by their teacher, yet its effects have not been experimentally studied. An empirical study pointed towards five factors that define students’ experience of being seen: The experience of their PE teachers caring, feedback, dialogue, and the opportunity for students to show their skills and being included in goal setting and evaluation in PE. This study aimed to investigate the impact of an intervention program designed to train physical education (PE) teachers in the concept of being seen.MethodsSix PE teachers and their students from a lower secondary school in Mid-Norway participated, with three teachers and their 68 students forming the control group, and three teachers and their 116 students forming the intervention group after random selection. A validated questionnaire assessing students’ perceptions of teacher care, feedback, dialogue, and opportunities to showcase skills was administered before and after a volleyball lesson. Following the initial lesson, intervention group teachers attended a course focusing on these four factors and applied them in a subsequent lesson. Data from 129 students (50 control, 79 intervention) were analyzed.ResultsThe results indicated significant differences in the intervention group compared to the control group in terms of maintaining the students’ experiences of teacher’s feedback, dialogue, and students’ ability to demonstrate skills. The intervention group showed slight increases in these factors, while the control group experienced decreases.DiscussionThese findings suggest that incorporating the concept of being seen into PE teaching practices can positively influence student experiences, and that teacher education should implement the concept in their teaching.